2023
DOI: 10.1111/scd.12855
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral odontogenic fibroma in a child with Ellis‐van Creveld syndrome: Case report

Abstract: IntroductionEllis‐van Creveld (EVC) syndrome is an autosomal recessive disorder predominantly characterized by a disproportionate dwarfism, ectodermal dysplasia, postaxial polydactyly, and congenital heart malformations and pulmonary hypoplasia.ObjectiveIn this article, we hereby present a case of a 6‐year‐old Brazilian boy with EVC syndrome who presented a rare oral lesion as well as a remarkable number of classical and uncommon oral and dental features.Case ReportClinical and radiographic examination reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Considering that 95% of POF cases occur in 10-19 years old pediatric patients, only few studies report of POF cases in children under 10 years [24]; for this reason, we decided to carry out a brief review of the relevant literature about POF in pediatric patients, and the results are presented as follows. Tomáz Ferraresso [25] described an interesting case of POF of the anterior mandible in a 6year-old patient, affected by Ellis-van Creveld (EVC) syndrome, an autosomal recessive disease consisting in skeletal and ectodermal dysplasia, characterized by short stature, postaxial polydactyly, ectodermal dysplasia, and congenital heart disease. The patient showed a small nodular neoformation on the edentulous alveolar ridge in the mandible, without radiological investigations, treated by conventional surgical excision, hemostasis and suture, without recurrence.…”
Section: Pof In Pediatric Patients: Analysis Of the Recent Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Considering that 95% of POF cases occur in 10-19 years old pediatric patients, only few studies report of POF cases in children under 10 years [24]; for this reason, we decided to carry out a brief review of the relevant literature about POF in pediatric patients, and the results are presented as follows. Tomáz Ferraresso [25] described an interesting case of POF of the anterior mandible in a 6year-old patient, affected by Ellis-van Creveld (EVC) syndrome, an autosomal recessive disease consisting in skeletal and ectodermal dysplasia, characterized by short stature, postaxial polydactyly, ectodermal dysplasia, and congenital heart disease. The patient showed a small nodular neoformation on the edentulous alveolar ridge in the mandible, without radiological investigations, treated by conventional surgical excision, hemostasis and suture, without recurrence.…”
Section: Pof In Pediatric Patients: Analysis Of the Recent Literaturementioning
confidence: 99%
“…The most reported and performed surgery consists of scalpel, followed by bone debridement, tooth scaling and root planning, with an approach that is as conservative as possible [39]. Of the 12 studies conducted on pediatric patients that we considered in this review, 9 authors have preferred this conventional treatment strategy because of its wellestablished reliability [8,11,14,20,25,26,28,29,32]. The remaining 3 authors reported the surgical excision of POF in newborns using diode laser [27,30,31].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%